Análisis de la demanda eléctrica en el alimentador N°1 de la subestación Pijilí a nivel de 13.8kV perteneciente a ELEPCO S.A para cuantificar las pérdidas técnicas y proponer mejoras en el sistema, en el año 2017. - Haro Haro, Juan Daniel (2018)
In this project presents the analysis and economic evaluation of technical losses that are generated in the feeder N°.1 of the S/E Pujilí. Through the collection and validation of information through frequency histograms, It is obtained the daily demand curve. Then is raised the theoretical and methodological bases for the determination of the factor of losses and load factor. Within the methodology was based on the bullfight, power flows through the Cymdist, which helped to determine the current status of the system, transformers, overloaded drivers and profiles of voltage, for the evaluation of the losses. It was decided to implement improvements in the system, with load balancing and bank of capacitors, these being two scenarios used in the improvement of the network. Culminating the analysis was carried out the economic valuation of losses resulting in a reduction of 6.78%, meaning that the implementation of the scenarios proposed in this research project is profitable.